Giant cell tumor of the thoracic spine: MR appearance. - Meyers, S P; Yaw, K; Devaney, K (American Journal of Neuroradiology, 1994)
The MR features of a giant cell tumor that predominantly involved the posterior elements of a thoracic vertebra are presented. This extradural neoplasm compressed and displaced the spinal cord. The tumor had low to intermediate signal on short-repetition-time images and predominantly high signal on long-repetition-time images. It showed mild heterogeneous enhancement with gadopentetate dimeglumine.